Understanding Gene Therapy in Acute Respiratory Distress Syndrome - Zhang, Xue-Peng; Zhang, Wei-Tao; Qiu, Yue; Ju, Min-Jie; Tu, Guo-Wei; Luo, Zhe (Current Gene Therapy, 2019)
Acute Respiratory Distress Syndrome (ARDS) and its complications remain lifethreatening conditions for critically ill patients. The present therapeutic strategies such as prone positioning ventilation strategies, nitric oxide inhalation, restrictive intravenous fluid management, and extracorporeal membrane oxygenation (ECMO) do not contribute much to improving the mortality of ARDS. The advanced understanding of the pathophysiology of acute respiratory distress syndrome suggests that gene-based therapy may be an innovative method for this disease. Many scientists have made beneficial attempts to regulate the immune response genes of ARDS, maintain the normal functions of alveolar epithelial cells and endothelial cells, and inhibit the fibrosis and proliferation of ARDS. Limitations to effective pulmonary gene therapy still exist, including the security of viral vectors and the pulmonary defense mechanisms against inhaled particles. Here, we summarize and review the mechanism of gene therapy for acute respiratory distress syndrome and its application.
Keywords: Gene therapy